PENENTUAN TARIF JASA KAMAR HOTEL DENGAN METODE ACTIVITY BASED COSTING SYSTEM PADA HOTEL GRAND VICTORIA DI SAMARINDA - Indri Kristiani; Set Asmapane; Fibriani Nur Khairin (Faculty of Economics and Business Mulawarman University, 2015)
Indri Kristiani, 2015 â€œHotel Room Service Rate Determination Method of Activity Based Costing System at Hotel Grand Victoria in Samarindaâ€, under the guidance of Mr. Set Asmapane (Supervisor 1) and Mrs. Fibriani Nur Khairin (Supervisor 2).The purpose of this research is to determine the determination of tariff for the hotel room in the Grand Victoria in Samarinda. Analyze used in this research is Activity Based Costing System. Activity Based Costing System is a method that traces the activity in the company. Further costs arising from these activities will be grouped cost pool based cost drivers that occurred.Based on the survey results revealed that the cost of a conventional system room for a superior room type is Rp 591.501/day, deluxe room type is Rp 668.726/day, junior suite room type is Rp 862.385/day, and victoria suite room type is Rp 1.245.518/day. While the cost of the room according to activity based costing system for a superior room type is for Rp 402.005/day, deluxe room type is Rp 453.188/day, junior suite room type is Rp 606.246/day, and victoria suite room type is Rp 1.063.762/day. Cost calculation of activity based costing system produces a lower rate compared with conventional system in all types of rooms. The difference is due to the lower cost of the activity based costing system is charged to many cost drivers while in the conventional system using only one or two cost drivers based unit.Â Â KeywordÂ Â Â Â Â Â Â Â : Â Â Â Â Â Activity Based Costing System, Cost Pool, and Cost Driver